Pengaruh Model Problem Based Learning Terhadap Kemampuan Literasi Sains Murid: Kajian Literatur - Wulandari Ramadhani; Ganda Hijrah Selaras; Fitri Arsih; Rahmi Kurniati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low scientific literacy skills of Indonesian students, as indicated by the results of the 2023 PISA (Philosophy of Biology), are a problem that requires serious attention in the world of education. This study aims to examine the influence of the Problem-Based Learning (PBL) model on students' scientific literacy skills in biology learning. The method used was a systematic literature review approach to eight articles from national journals published in the last five years. The results of the study showed that all articles consistently demonstrated the positive and significant influence of the PBL model on students' scientific literacy skills in various biology materials, such as the excretory system, environmental change, and viruses. The advantage of PBL lies in its contextual problem-based approach that encourages students to think critically, conduct scientific inquiries, and integrate scientific concepts with real-life situations. The integration of PBL with the STEM approach has also been shown to further optimize the improvement of scientific literacy. It is concluded that the PBL model is an effective learning strategy and is recommended for improving students' scientific literacy skills in biology learning.